Reading Comprehension Strategy Use and Related Difficulties among English-Majored Students at Thu Dau Mot University - Ngo Huong Hoa (Technium Social Sciences Journal, 2026)
Reading comprehension strategies play a crucial role in helping English as a Foreign Language (EFL) learners process texts effectively and achieve deeper understanding. However, many university students still encounter difficulties in using these strategies appropriately. This study investigates the use of reading comprehension strategies and related difficulties among English-majored students at Thu Dau Mot University in Vietnam. A mixed-method design was employed, combining questionnaires and semi-structured interviews with both students and teachers. Quantitative data were collected from 129 English-major students and 19 English lecturers and analyzed using descriptive statistics and one-way ANOVA, while qualitative data were used to provide further explanation of the quantitative findings. The results indicate that although students reported using a range of reading and comprehension strategies, many of them relied on less effective practices. In particular, students tended to begin reading immediately without sufficient planning, showed limited use of previewing, and depended heavily on underlining or highlighting rather than more elaborative note-taking strategies. In addition, many students relied on dictionaries rather than contextual guessing, frequently translated and remembered texts in Vietnamese, and experienced difficulty summarizing what they had read. Freshmen were found to experience more problems than more advanced students in several areas of strategy use. The study highlights the need for more explicit and sustained instruction in reading strategies to help English-majored students become more effective, strategic, and independent readers in EFL contexts.